Dual Faces Architecture of Nias - Meridiani Trianandari Wananto; Afina Rahmani; Dadi Satria Ginandjar; Angga Kusumah Sukarya; Shirley Wahadamaputera (REKA KARSA)
Abstract Many Indonesian people built a traditional house based on beliefs of their ancestors for generations, without knowing the scientific reason. Meanwhile, indirectly, ancestors already thinking about housing that adapts the environmental conditions such as in Nias Island. Nias is an island that has two different forms of traditional houses which are affected by the differences geographic, highland and lowland. Geographic factors and beliefs not only affect the shape of the house but also the structure of the house. Located on the earthquake fault lines, Nias traditional houses was designed to withstand earthquakes that often befall. A study using description and analysis methods about design and structure which used in traditional houses in Nias Island, would develop a good sense of the idea to apply these materials on modern building to preserve the culture of Indonesia. Key Words: Nias Island, Nias Traditional House, Earthquake, Building Material